Israel's place in the Middle East a pluralist perspective - Rejwan, Nissim 1924- (Univ. Press of Florida, 1998)
Rejwan points out the error of those who think that Jews and Arabs stand in opposition, representing two confliction cultures, mentalities and temparatments, examines Israel's place in the Middle East from historical, religious and cultural perspectives.
Keywords: Geschichte Anfänge-1998; Arabieren; Buitenlandse betrekkingen; Culturele betrekkingen; Joden; Außenbeziehungen; Außenpolitik; Geschichte; Juden; Judentum; Nahostkonflikt; Politik; Arab-Israeli conflict; Islam -- Relations -- Judaism; Jewish-Arab relations -- History; Judaism -- Relations -- Islam; Araber; Kulturelle Identität; Herkunft; Beziehung; Naher Osten; Israel -- Foreign relations -- Middle East; Israel -- Politics and government; Middle East -- Foreign relations -- Israel; Israel